“It’s Not the Materials Themselves, It’s the Attitude of the Donors”: The Role of Community Accountability in the Sustainability of Queer Archives - Wagner, Travis; Martell, Allan; Oltmann, Shannon (Archivaria, 2024)
This article reports on findings from semi-structured interviews with 25 archivists and curators who work with LGBTQIA+-related collections and materials about the HIV/AIDS epidemic. Specifically, it reports on how these practitioners define and engage with ethical practices, access-based obligations, and community relations in creating and sustaining their archives. The article focuses on how participants, including practitioners from various community and institutional archives of varying size and scope across the United States, understood community accountability within their work. This emphasis on community accountability necessitated that practitioners reframe archival ethics, reconsider subjective and embodied collection and curation work, and prioritize community well-being over quantitative collection building. In response to these findings, the article identifies theoretical and practical implications for queer archives related to methods of archival production, approaches to community outreach and engagement, and the intersecting impact of these implications and approaches on questions of archival sustainability for queer and other historically marginalized histories.